84 An Analysis into the Prevalence of Work-Related Musculoskeletal Disorders Affecting Surgeons: A Systematic Review. (19th August 2022) - Daruwalla, AC; Patel, B
Abstract: Aim: This review sought to answer 3 primary questions- (1) What is the global career prevalence rate of work-related musculoskeletal disorders (WRMSDs) among the surgeon population? (2) What is the prevalence rate of WRMSDs between surgical specialties? and (3) Which anatomical locations are most affected in surgeons with WRMSDs? Method: A qualitative systematic review of publications was conducted across 4 medical indices, 3 clinical trial registries, and 2 specialised search engines for relevant records published from inception until the 31st of December 2020. The JBI checklist and ROBINS-I tool were used for quality and risk assessment among included studies. Results: In total, 56 articles met the inclusion criteria set for this review. This gave a pooled total of 13, 628 surgeons. From this population, the calculated career prevalence rate of WRMSDs was found to be 71.1%, and the specialties with the highest incidences of WRMSDs were- Dermatology surgery (90.1%), Obstetrics and Gynaecology surgery (81.4%), and Vascular surgery (80.0%). When analysing body regions most frequently affected by WRMSDs, 91.3% of injuries were reported above the waist. More specifically, the most frequently reported injuries were to the back (30.4%), neck (26.2%), and shoulders (16.0%). Conclusions: Overall, this review found high career prevalence rates of WRMSDs across all analysed surgical specialties. Furthermore, these injuries were most frequently reported in the upper limb and torso of the surgeon. With these findings, it is hoped future interventional studies would aim to target specific ergonomic deficits in specialties at high risk of developing WRMSDs.